Vascularized 3D human skin models in the forefront of dermatological research - Rimal, Rahul; Muduli, Saradaprasan; Desai, Prachi; Marquez, Andrea Bonnin; Möller, Martin; Platzman, Ilia; Spatz, Joachim P.; Singh, Smriti (Advanced healthcare materials, 2024)
In vitro engineered skin models are emerging as an alternative platform to reduce and replace animal testing in dermatological research. Despite the progress made in recent years, considerable challenges still exist for the inclusion of diverse cell types within skin models. Blood vessels, in particular, are essential in maintaining tissue homeostasis and are one of many primary contributors to skin disease inception and progression. Substantial efforts in the past have allowed the successful fabrication of vascularized skin models that are currently utilized for disease modeling and drugs/cosmetics testing. This review first discusses the need for vascularization within tissue-engineered skin models, highlighting their role in skin grafting and disease pathophysiology. Second, the review spotlights the milestones and recent progress in the fabrication and utilization of vascularized skin models. Additionally, advances including the use of bioreactors, organ-on-a-chip devices, and organoid systems are briefly explored. Finally, the challenges and future outlook for vascularized skin models are addressed.
Zuerst veröffentlicht: 26. Januar 2024
Gesehen am 11.06.2024